Antihypertensive effect of peptides naturally generated during Iberian dry-cured ham processing. (December 2015) - Mora, Leticia; Escudero, Elizabeth; Arihara, Keizo; Toldrá, Fidel
Abstract: Iberian dry-cured ham is considered a product of excellence in Spain and also highly valued by consumers overseas. Its processing conditions include a minimum time of ripening of 24 months which results on a very intense proteolysis of muscular proteins due to the action of endogenous enzymes and the generation of numerous peptides and free amino acids responsible for its characteristic flavour properties. Previous studies in Spanish dry-cured ham of 10 months of ripening identified the amino acid sequences of many of the peptides generated during the proteolysis as well as described their potential as bioactive peptides. However, differences in genetics and processing conditions such as the time of ripening, could result on differences in the action of endogenous enzymes and the generated peptides. In this study, differences in the generated peptides between Iberian dry-cured (24 months of ripening) and traditional Spanish dry-cured ham (14 months of ripening) have been detected. Iberian dry-cured ham extract was separated using size-exclusion chromatography and the ACE-inhibitory activity of the obtained fractions was evaluated in vitro showing up to 97.7% of inhibition in some of the fractions. The antihypertensive effect of the Iberian ham extract was also assayed in vivo using spontaneously hypertensive rats. A significant decrease of 12 mm Hg in SBP after 8 h of ingestion ( p < 0.05) that returned to values similar to the control after 24 h of the treatment was observed. The analysis by mass spectrometry in tandem of the peptide extract revealed a total of 2632 peptides which contained the ACE inhibitory Pro–Pro–Lys, Pro–Ala–Pro, and Ala–Ala–Pro repeated in their sequences a total of 322, 302 and 119 times, respectively. This study reveals Iberian dry-cured ham as a source for natural antihypertensive peptides with very high potential in comparison with Spanish dry-cured ham, probably due to the differences in genetics and time of ripening which influence proteolysis and thus the generation of peptides. Highlights: Antihypertensive peptides extracted from Iberian dry-cured ham Iberian ham peptides assayed for in vitro ACE assay and in vivo antihypertensive activity Iberian dry-cured ham as a source of antihypertensive peptides naturally generated during the dry-curing process.